Thermal transfer film and image forming method - TORII MASANORI; CHUJO SHIGEKI; MIZUKAMI FUMIHIKO; MAEDA MITSURU (2003)
A thermal transfer film comprises a coloring layer formed on a substrate film via an intermediate layer, wherein the intermediate layer contains a thermally fusible substance and a non-transferable binder resin, the melt viscosity of the thermally fusible substance in the temperature range 15 to 25° C. higher than the fuse peak temperature of the thermally fusible substance is in the range of 100 to 1000 mPa.s, the fuse peak temperature of the thermally fusible substance is in the range of 50 to 110° C., the crystallization peak temperature of the thermally fusible substance is in the range of -20 to 100 ° C., the crystallization peak temperature of the thermally fusible substance is lower than the fuse peak temperature by 10° C. or more, and the softening temperature of the binder resin measured by the ring and ball method is in the range of 130 to 400 ° C. This thermal transfer film is capable of forming a printed product with a good printing quality.